Perkawinan Beda Agama dan Implikasinya Terhadap Terbitnya Kartu Keluarga Perspektif Undang-undang No. 1 Tahun 1974 dan Undang-undang No. 23 Tahun 2006 : (Studi Kasus Kecamatan Naman Teran, Kabupaten Karo) - Wike Sundari; Amal Hayati (Universitas Ekasakti, 2024)
Marriage is a spiritual and physical relationship between a man and a woman as husband and wife, with the goal of creating a happy family based on the belief in the Almighty God. One of the marriages that often occurs in Indonesia is marriage between different religions. Law Number 1 of 1974 outlaws interfaith marriages, as stated in article 2 paragraph 1: